PENGEMBANGAN PERANGKAT PEMBELAJARAN MEMBACA PEMAHAMAN MENGGUNAKAN GRAPHIC ORGANIZER PLOT DIAGRAM UNTUK KELAS VI SEKOLAH DASAR - Delita Gustriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2017)
ABSTRACT Teachers have responsibility to create and develop an effective learning instruments in order to facilitate the student to understand the reading content optimally. Unfortunately, not all teachers are able to accept and run that responsibility. There are, it is important to develop an effective learning instruments by using Graphic Organizer Plot Diagram as the solusion. The learning instruments were developed by using 4-D model (Defining, Designing, Developing, and Disseminating). The design was validated by four experts and three educational practitioners. To see the practicality and the effectiveness of the instruments developed, it then was tried out limitedly to the students in class VI of SDN 18 Air Tawar Selatan. The disseminating phase, however, was done in a limited scale. The result of the research indicated that the validity rate into the category of highly valid. Then upon the assessment on the implementation of lesson plan, the responses from teachers and learning participants and the observations on teaching materials indicated that the practicality rate fell to the category of highly practical. Moreover, the result of the activity of learning participants on reading comprehension indicated to be effective. Based on the result of the research, it was concluded that the Graphic Organizer Plot Diagram strategy-oriented reading comprehensionlearning instruments developed had been valid, practical, and effective. Keywords: Learning Instruments, Reading Comprehension, Graphic Organizer Plot Diagram. ABSTRAK Guru memiliki tanggung jawab untuk membuat dan mengembangkan instrumen pembelajaran yang efektif untuk memudahkan siswa memahami isi bacaan secara optimal. Sayangnya, tidak semua guru dapat menerima dan menjalankan tanggung jawab itu. Ada, penting untuk mengembangkan instrumen pembelajaran yang efektif dengan menggunakan Graphic Organizer Plot Diagram sebagai solusinya. Instrumen pembelajaran dikembangkan dengan menggunakan model 4-D (Mendefinisikan, Merancang, Mengembangkan, dan Menyebarluaskan). Desain ini divalidasi oleh empat ahli dan tiga praktisi pendidikan. Untuk melihat kepraktisan dan keefektifan instrumen yang dikembangkan, kemudian diadili secara terbatas kepada siswa di kelas VI SDN 18 Air Tawar Selatan. Namun fase penyebarluasan dilakukan dalam skala terbatas. Hasil penelitian menunjukkan bahwa tingkat validitas masuk dalam kategori sangat valid. Kemudian setelah penilaian pada pelaksanaan rencana pelajaran, tanggapan dari guru dan peserta belajar dan pengamatan pada bahan ajar menunjukkan bahwa tingkat kepraktisan jatuh ke kategori sangat praktis. Selain itu, hasil dari aktivitas peserta belajar membaca pemahaman diindikasikan efektif. Berdasarkan hasil penelitian, disimpulkan bahwa Grafik Organiser Plot Diagram yang berorientasi pada strategi membaca pemahaman instrumen pembelajaran yang dikembangkan telah valid, praktis, dan efektif. Kata kunci: Instrumen Pembelajaran, Pemahaman Membaca, Diagram Plot Grafis